An In-depth Look at TOI-3884b: A Super-Neptune Transiting an M4Dwarf with Persistent Starspot Crossings - Jessica E. Libby-Roberts; Maria Schutte; Leslie Hebb; Shubham Kanodia; Caleb I. Cañas; Guðmundur Stefánsson; Andrea S. J. Lin; Suvrath Mahadevan; Winter Parts(they/them); Luke Powers; John Wisniewski; Chad F. Bender; et al. (The Astronomical Journal, 2023)
We perform an in-depth analysis of the recently validated TOI-3884 system, an M4-dwarf star with a transiting super-Neptune. Using high-precision light curves obtained with the 3.5 m Apache Point Observatory and radial velocity observations with the Habitable-zone Planet Finder, we derive a planetary mass of ${32.6}_{-7.4}^{+7.3}\,M_{\oplus }$ and radius of 6.4 ± 0.2 R _⊕ . We detect a distinct starspot crossing event occurring just after ingress and spanning half the transit for every transit. We determine this spot feature to be wavelength dependent with the amplitude and duration evolving slightly over time. Best-fit starspot models show that TOI-3884b possesses a misaligned ( λ = 75° ± 10°) orbit that crosses a giant pole spot. This system presents a rare opportunity for studies into the nature of both a misaligned super-Neptune and spot evolution on an active mid-M dwarf.